Clinical case report on treatment of Listeria monocytogenes meningoencephalitis: Intrathecal injection - Pan, Xu‐Biao (Clin Case Rep, 2018)
This article mainly reports the process of clinical diagnosis and treatment of a misdiagnosed Listeria monocytogenes meningoencephalitis. The patient's condition is aggravated because of the ineffective prophase therapy. In the later stage, we were mainly through combined antibiotics and given proper routes of administration, so that patient can recover quickly.